2023
DOI: 10.3390/ijms24054883
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways Implicated in Radioresistance of Glioblastoma Multiforme: What Is the Role of Extracellular Vesicles?

Abstract: Glioblastoma multiforme (GBM) is a primary brain tumor that is very aggressive, resistant to treatment, and characterized by a high degree of anaplasia and proliferation. Routine treatment includes ablative surgery, chemotherapy, and radiotherapy. However, GMB rapidly relapses and develops radioresistance. Here, we briefly review the mechanisms underpinning radioresistance and discuss research to stop it and install anti-tumor defenses. Factors that participate in radioresistance are varied and include stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 269 publications
0
5
0
Order By: Relevance
“…Despite extensive studies on GBM resistance to radiotherapy, its mechanisms are still largely not understood because of the multifactorial and heterogeneous nature of this phenomenon. Many factors have been involved in GBM resistance to radiotherapy: intra-, inter-tumor heterogeneity and tumor plasticity, aberrant expression of non-coding RNAs (ncRNAs), metabolic and epigenetic reprogramming, alterations in DNA repair and cell cycle [ 3 ]. Among these, the existence of a rare population of self-renewing stem-like cells able to sustain tumor initiation and growth, to contribute to therapy resistance and recurrence of the disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive studies on GBM resistance to radiotherapy, its mechanisms are still largely not understood because of the multifactorial and heterogeneous nature of this phenomenon. Many factors have been involved in GBM resistance to radiotherapy: intra-, inter-tumor heterogeneity and tumor plasticity, aberrant expression of non-coding RNAs (ncRNAs), metabolic and epigenetic reprogramming, alterations in DNA repair and cell cycle [ 3 ]. Among these, the existence of a rare population of self-renewing stem-like cells able to sustain tumor initiation and growth, to contribute to therapy resistance and recurrence of the disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM), the most malignant form of astrocytoma, represents a paramount challenge in neuro-oncology due to its aggressive spreading growth pattern and complex pathophysiology (Burko et al 2023 ; Wang et al 2023 ). The current standard treatment modalities for GBM include surgical resection followed by adjuvant radiation therapy and chemotherapy with temozolomide (Clavreul et al 2022 ; Raue et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the elimination of glioma stem cells is presumed to be an integral step in achieving long-term survival and, ultimately, a cure for this lethal disease by preventing tumor recurrence [9][10][11]. However, difficulties are associated with identifying cytotoxic agents that eliminate glioma stem cells due to the markedly stronger resistance of glioma stem cells to conventional chemo-and radiotherapies than their differentiated, non-stem cell progeny [6,12]. Intriguingly in this regard, we and others have revealed that glioma stem cells have unique vulnerabilities that render them "more sensitive" to certain drugs than their non-stem cell progeny [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%